Oral cancer in Hungary: An epidemiological profile (2015–2019) - Amr Sayed Ghanem; Laszlo Trefan; Ildikó Márton; Petra Fadgyas-Freyler; Attila Csaba Nagy; Marianna Móré (PLoS ONE, 2025)
Objective Hungary is among countries with the highest standardised rate oral and mouth cancers. This first national analysis aimed to quantify age-standardized oral cancer incidence in Hungary from 2015 to 2019 by sex and age, determine the median interval from diagnosis to death, and evaluate comorbidity prevalence and its prognostic impact. Methods We used real-world data from the Hungarian National Health Insurance Fund database. Adjusted, standardised incidence- and hospital readmission rates were calculated; time between diagnosis and death and effect of comorbidities coexisting with oral cancer were analysed. Results Generally, incidence and hospitalisation rates decreased in the studied period, for males and older age group both rates were higher. From year 2017 for incidence rates significant differences were found between a particular region and the other regions; and hospitalisation rates differed significantly for three regions from other regions. Almost half (46.3%) of the patients died within a year after diagnosis, mortality rates were 31.8% for males and 14.5% for females. Existence of oral cancer indicated 5.20 (95% confidence interval, 5.03,5.38), 5.84 (95% confidence interval, 5.64,6.04) odd ratios for mortality by two models. Number and relative risk of comorbidities were higher among patients diagnosed with oral cancer than in the control population. Conclusion The study highlighted progress in reducing oral cancer incidence rates in Hungary, however significant challenges remain in reducing mortality rates and improving survival within the first year of diagnosis. The study also showed oral cancer a serious burden in the country, especially for males.